2012
DOI: 10.1523/jneurosci.1436-12.2012
|View full text |Cite
|
Sign up to set email alerts
|

3Is Required for Normal Light ON Responses and Synaptic Maintenance

Abstract: Heterotrimeric G-proteins, comprising Gα and Gβγ subunits, couple metabotropic receptors to various downstream effectors and contribute to assembling and trafficking receptor based signaling complexes. A G-protein β-subunit, Gβ3 plays a critical role in several physiological processes as a polymorphism in its gene is associated with a risk factor for several disorders. Retinal ON bipolar cells express Gβ3, and they provide an excellent system to study its role. In the ON bipolar cells, mGluR6 inverts the photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
60
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 57 publications
5
60
0
Order By: Relevance
“…As shown previously, staining for mGluR6 was also slightly reduced (Fig. 8, right column) (26). Unlike Gnb3-null retina, staining of Gnao1 (gene encoding G␣ o1 )-null retina was not much different from the wild type (data not shown).…”
Section: Kir24 In the Dendritic Tips Of Retinal On Bipolar Cells Is supporting
confidence: 82%
See 1 more Smart Citation
“…As shown previously, staining for mGluR6 was also slightly reduced (Fig. 8, right column) (26). Unlike Gnb3-null retina, staining of Gnao1 (gene encoding G␣ o1 )-null retina was not much different from the wild type (data not shown).…”
Section: Kir24 In the Dendritic Tips Of Retinal On Bipolar Cells Is supporting
confidence: 82%
“…A role for G␤␥ in trafficking is also supported by studies in neural tissue. We have recently shown that in retinal ON bipolar cells lacking G␤3 (a subunit that mediates their light responses by coupling the metabotropic mGluR6 receptor to the TRPM1 channel), numerous elements that play an important role in the mGluR6 cascade are downregulated or redistributed (26). This includes not only the G-protein subunit partners, but also the receptor mGluR6 and the channel TRPM1.…”
Section: Discussionmentioning
confidence: 99%
“…A G-protein β subunit, Gβ3 3 , is expressed in ON-bipolar cells and plays an essential role for proper localization of mGluR6 and TRPM1 on rod bipolar dendrites (Dhingra et al 2012). Activation of PKCα reduces the inhibition of Trpm1 function by Mg 2+ (Rampino and Nawy 2011).…”
Section: Application Of Another G-protein Subunit Gβγ Did Not Supprmentioning
confidence: 99%
“…A strong body of evidence indicates that Gβ3 constitutes the major isoform involved in ON-BC signal transduction. Gβ3 is expressed prominently and specifically in ON-BCs (Dhingra et al 2012, Huang et al 2003, Peng et al 1992) and its knockout severely reduces the amplitude of depolarizing responses of both ON-RBCs and ON-CBCs (Dhingra et al 2012). Similarly, Gγ13 was described as the most prominent isoform present in ON-BCs (Dhingra et al 2008, Huang et al 2003).…”
Section: Heterotrimeric G Proteins Transfer Light-evoked Signals Frommentioning
confidence: 99%